(untitled)
Let B_n(z),n = 0,1,..., be the Bessel polynomials generated by \[(1 - 4zw)^-1/2exp{ 1 - (1 - 4zw)^1/2 2z}=_n=0^∞B_n(z)w^n, |4zw| < 1\] and the functions B_n(z) be defined by the relations \[B_n(z)=4^-nz^nB_n(1/z)exp(-z/2).\] Let K = {k_n}_n=0^∞ be an increasing sequence of non-negative integers. Sufficient conditions for the completeness of the systems {B_k_n (z)}_n=0^∞ and {B_k_n (z)}_n=0^∞ in spaces of holomorphic functions are given in terms of the density of the sequence K. , journal=Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, year=1997, month=Dec., pages=79–88